Implementation of Digital Fairy Tales in an Effort to Cultivate Character in Children Aged 5-6 Years - Khotimah, Mutiara Khusnul; Cholimah, Nur (Jurnal Pendidikan Anak, 2025)
This study aimed to describe the implementation of digital fairy tales in an effort to instill characters in children aged 5-6 years. The method used in this study was descriptive of the type of case study research. The data sources taken included two teachers, one principal, and 10 children aged 5-6 years. Then, the techniques used in this study consist of observation, interviews, and documentation. Furthermore, the data obtained was analyzed using the stages of data reduction, data display, and drawing a conclusion. This study found that the implementation of digital fairy tales in an effort to build the character of children aged 5-6 years at school applied the strategy from Lickona. These strategies include moral knowing, which is applied by conveying understanding and comprehension of character; moral feeling, which is applied by building understanding and mindset in children; and moral action, which is applied by carrying out good character habits.